STRATEGI PEMASARAN SOSIAL PONDOK PESANTREN DALAM PENGEMBANGAN MASYARAKAT ISLAM - Dede Sa'adah (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2019)
Qothrotul Falah is the Islamic traditional education (pesantren) based on salafi approach. In the research process, the article the focused on issues that has formulated related to the topic of social marketing and marketing strategy, which is implementing by pesantren of Qothrotul Falah. This study aims: 1) to identify the education marketing strategy at the pesantren of Qothrotul Falah, and 2) to analyze the social marketing to improve educational strategy in the competitive era. The method of this research used qualitative research that had developed with descriptive analysis. This study finding that the educational marketing which had been implementing by Qothrotul Falah consist fourteen (40) types: Kyai, writing skills, publications (Mass Media, Banner, Brochure, Calendar, Bulletin, Radio Broadcasting), social media (Facebook, Instagram, Website, WhatsApp), community participation, and alumni. According to educational development in the competitive era, Head of pesantren had been responding its conditions. For example, he included the modern system of Arabic teaching, English and established formal education (Junior and Senior Islamic Schools), and several supporting activities for studenst, including: Student Organizations, Scouting, Student Health Organization, Sports, Music, Marawis, Computer Course, Muhadharah and Qira'ah al-Qur'an.